2022
DOI: 10.3389/fgene.2021.796060
|View full text |Cite
|
Sign up to set email alerts
|

Small Open Reading Frames, How to Find Them and Determine Their Function

Abstract: Advances in genomics and molecular biology have revealed an abundance of small open reading frames (sORFs) across all types of transcripts. While these sORFs are often assumed to be non-functional, many have been implicated in physiological functions and a significant number of sORFs have been described in human diseases. Thus, sORFs may represent a hidden repository of functional elements that could serve as therapeutic targets. Unlike protein-coding genes, it is not necessarily the encoded peptide of an sORF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…We did not discuss molecular tools that are available to determine whether these upORFs could be at the origin of functional small micropeptides that could have specific physiological roles. This topic has recently been addressed in an independent review ( 28 ). Finally, we only examined in this work SNVs that could create uAUG resulting upORFs, the most known class of variants among those that affect non-canonical ORFs.…”
Section: Discussion/perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not discuss molecular tools that are available to determine whether these upORFs could be at the origin of functional small micropeptides that could have specific physiological roles. This topic has recently been addressed in an independent review ( 28 ). Finally, we only examined in this work SNVs that could create uAUG resulting upORFs, the most known class of variants among those that affect non-canonical ORFs.…”
Section: Discussion/perspectivesmentioning
confidence: 99%
“…These assays are based on the cloning of the entire promoter of a given transcript before the coding sequence of a luciferase and the evaluation of the promoter activity in wild-type and mutant contexts in vitro by measuring the obtained luciferase luminescence normalized to a control vector. Additional methods used to characterize small ORFs and their potential translation into SEPs has been recently reviewed in ( 28 ). Altogether, upSNVs are still a neglected class of non-coding variations, and are often called as Variants of Unknown Significance when they are identified in routine clinical diagnosis, contributing then to medical wandering.…”
Section: Introductionmentioning
confidence: 99%
“…(Derrien et al, 2012;Alessio et al, 2020). Previous studies have reported that lncRNAs are unable to encode proteins, but recent investigations have identified abundant small open reading frames in lncRNAs via ribosomal analysis, some of which have the potential to encode micro-peptides and proteins (Kong et al, 2020;Ye et al, 2020;Zhou B. et al, 2021;Kute et al, 2021). RNA polymerase II (Pol II) transcribes protein-encoding genes and numerous pre-messenger RNAs (mRNAs) of lncRNAs, including long intergenic non-coding RNAs (lincRNAs), enhancer RNAs, antisense RNAs, and promoter upstream transcripts (Nojima and Proudfoot, 2022).…”
Section: Figurementioning
confidence: 99%
“…( Derrien et al, 2012 ; Alessio et al, 2020 ). Previous studies have reported that lncRNAs are unable to encode proteins, but recent investigations have identified abundant small open reading frames in lncRNAs via ribosomal analysis, some of which have the potential to encode micro-peptides and proteins ( Kong et al, 2020 ; Ye et al, 2020 ; Zhou B. et al, 2021 ; Kute et al, 2021 ).…”
Section: Biogenesis Degradation and Exosome Formation Of Lncrnasmentioning
confidence: 99%
“…Their minuscule size has caused them to be excluded from most gene prediction methods (Couso and Patraquim, 2017). The length cut-off filter used in most gene prediction methods is 300 bp and any sequences below this cut-off will be considered as being non-functional (Kute et al, 2022).…”
Section: Introductionmentioning
confidence: 99%